2016
DOI: 10.1002/aur.1653
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between pain sensitivity and empathic response in adolescents with autism spectrum conditions and conduct disorder symptoms

Abstract: Lack of empathy is one of the behavioral hallmarks in individuals with autism spectrum conditions (ASC) as well as youth with conduct disorder symptoms (CDS). Previous research has reliably documented considerable overlap between the perception of others' pain and first-hand experience of pain. However, the linkage between empathy for pain and sensitivity to physical pain needs to be empirically determined, particularly in individuals with empathy deficits. This study measured the pressure pain threshold, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 54 publications
0
15
0
1
Order By: Relevance
“…ASD are complex neurodevelopmental diseases whose diagnosis is based on the detection of two types of behavioural symptoms (core symptoms): impaired social reciprocity and communication together with restricted, repetitive patterns of behaviour, interests or activities (Diagnostic and Statistical Manual of Mental Disorders: DSM‐5). Co‐morbid symptoms, variable in their occurrence and intensity, are frequently associated with ASD and encompass anxiety disorders, cognitive and motor deficits, aggressive behaviour, epileptic episodes, sleep disturbances, increased sensitivity to pain and altered gastrointestinal transit (Johnson and Myers, ; Robinson, ; Veenstra‐VanderWeele and Blakely, ; White et al , ; Mazurek et al , ; Whyatt and Craig, ; Chen et al , ). Intriguingly, in addition to deficits in social behaviour, Oprm1 −/− mice show stereotyped and perseverative behaviours, necessary to fulfil ASD criteria, as well as many of the co‐morbid symptoms of ASD, namely, increased aggressiveness, exacerbated anxiety and motor clumsiness (Becker et al , ), increased susceptibility to seizures (Jang et al , ; Grecksch et al , ; Becker et al , ), impaired spatial learning (Jamot et al , ), lowered nociceptive thresholds (Gaveriaux‐Ruff and Kieffer, ) and reduced gastrointestinal motility (Roy et al , ).…”
Section: Genetic Manipulations Of the μ Opioid Receptor And Autistic‐mentioning
confidence: 99%
“…ASD are complex neurodevelopmental diseases whose diagnosis is based on the detection of two types of behavioural symptoms (core symptoms): impaired social reciprocity and communication together with restricted, repetitive patterns of behaviour, interests or activities (Diagnostic and Statistical Manual of Mental Disorders: DSM‐5). Co‐morbid symptoms, variable in their occurrence and intensity, are frequently associated with ASD and encompass anxiety disorders, cognitive and motor deficits, aggressive behaviour, epileptic episodes, sleep disturbances, increased sensitivity to pain and altered gastrointestinal transit (Johnson and Myers, ; Robinson, ; Veenstra‐VanderWeele and Blakely, ; White et al , ; Mazurek et al , ; Whyatt and Craig, ; Chen et al , ). Intriguingly, in addition to deficits in social behaviour, Oprm1 −/− mice show stereotyped and perseverative behaviours, necessary to fulfil ASD criteria, as well as many of the co‐morbid symptoms of ASD, namely, increased aggressiveness, exacerbated anxiety and motor clumsiness (Becker et al , ), increased susceptibility to seizures (Jang et al , ; Grecksch et al , ; Becker et al , ), impaired spatial learning (Jamot et al , ), lowered nociceptive thresholds (Gaveriaux‐Ruff and Kieffer, ) and reduced gastrointestinal motility (Roy et al , ).…”
Section: Genetic Manipulations Of the μ Opioid Receptor And Autistic‐mentioning
confidence: 99%
“…The empirical literature search resulted in 4769 citations. After title and abstract screening was completed, 413 full-text studies were reviewed, and data was extracted and charted from 66 studies that fulfilled all eligibility criteria [ 15 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Some of these studies are case studies, whereas others are in the form of empirical studies. The pressure pain threshold was measured in a study, which indexes sensitization of peripheral nociceptors, and assessed subjective ratings of unpleasantness and pain intensity in response to empathy-eliciting stimuli depicting physical bodily injuries in three age-and sex-matched participant groups; namely, ASD, conduct disorder symptoms (CDS), and typically developing controls (TDC) [29]. Their findings indicated that the pain threshold was lowest in the ASD group and highest in the CDS group.…”
Section: Discussionmentioning
confidence: 99%